2018
DOI: 10.1039/c7cc07332a
|View full text |Cite
|
Sign up to set email alerts
|

Radical halogenation-mediated latent–active glycosylations of allyl glycosides

Abstract: Radical halogenation-mediated glycosylation using allyl glycosides as donors and as acceptors emerges to be an efficient and hither-to unknown glycosylation method, adhering to the concept of the latent-active methodology. Several di- and trisaccharides that possess the allyl moiety at their reducing end are prepared through this new glycosylation methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Allylic halogenation under photochemical condition was developed by Diaz and co‐workers as a method to deprotect the anomeric allyl moiety of a sugar [72] . Realizing that radical halogenation is a facile reaction, [73] efforts were undertaken to explore the allylic halide ( I ) as a glycosyl donor, promoted by a suitable catalyst. For this purpose, the sugar allylic halides were prepared first by radical halogenation of allyl glycosides (Figure 5).…”
Section: Exocyclic Unsaturation As a Tool For Glycosylationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allylic halogenation under photochemical condition was developed by Diaz and co‐workers as a method to deprotect the anomeric allyl moiety of a sugar [72] . Realizing that radical halogenation is a facile reaction, [73] efforts were undertaken to explore the allylic halide ( I ) as a glycosyl donor, promoted by a suitable catalyst. For this purpose, the sugar allylic halides were prepared first by radical halogenation of allyl glycosides (Figure 5).…”
Section: Exocyclic Unsaturation As a Tool For Glycosylationsmentioning
confidence: 99%
“…Further studies showed that a halophilic reagent, such as, AgOTf, as a promoter of the allylic halide II mediated the glycosylation of acceptor alcohols ( III ), leading to the formation of the glycoside ( IV ). Reiteration of allylic halogenation to intermediate V and glycosylation with III afforded VI [73] …”
Section: Exocyclic Unsaturation As a Tool For Glycosylationsmentioning
confidence: 99%
“…A newer allylic glycoside activation was developed recently in our research group [43]. The newly developed synthetic method combines radical-mediated activation of an allyl glycoside to an allyl halide, which upon reaction with a glycosyl and aglycosyl acceptor in the presence of an acid promoter leads to a glycoside product.…”
Section: (Ii) Allylic Halide Activation Of Allyl Glycosidesmentioning
confidence: 99%
“…Fig. 4: A scheme of latent-active glycosylation involving an allyl glycoside, initiated by a radical-mediated allylic halogenations [43]. A change of the protecting group from O-acetyl to O-benzoyl on the donor moiety increased the yield of the glycosylation product.…”
Section: (Latent)mentioning
confidence: 99%